Compensation and Pension Bills for Veterans and Their Dependents : hearings before the United States House Committee on Veterans Affairs, Subcommittee on Compensation and Pension, Eighty-Third Congress, second session, on Mar. 31, Apr. 1, 2, 6, 1954. (U.S. Congressional Hearings., 1954)
Includes numerous submitted VA and other Federal agency reports.